Nucleosynthesis during the merger of white dwarfs and the origin of R coronae borealis stars - Longland, R. (2011)
Many hydrogen-deficient stars are characterized by surface abundance patterns that are hard to reconcile with conventional stellar evolution. Instead, it has been suggested that they may represent the result of a merger episode between a helium and a carbon-oxygen white dwarf. In this Letter, we present a nucleosynthesis study of the merger of a 0.4 M O helium white dwarf with a 0.8 M O carbon-oxygen white dwarf, by coupling the thermodynamic history of Smoothed Particle Hydrodynamics particles with a post-processing code. The resulting chemical abundance pattern, particularly for oxygen and fluorine, is in qualitative agreement with the observed abundances in R Coronae Borealis stars.